Quantitative analysis of total methenolone in animal source food by liquid chromatography‐tandem mass spectrometry. Issue 1 (6th September 2020) - Zheng, Junping; Ye, Cheng; Wang, Peng; Liu, Yang; Yang, Huabing; Liu, Hongtao
Abstract: Methenolone, an anabolic androgenic steroid, has been applied to improve the quality and protein content of meat in animal husbandry. However, the usage of methenolone in sports is banned for its doping effects. Several methods have been reported to monitor the content of methenolone in serum and urine samples, but a highly sensitive detection system has not been developed for the determination of methenolone in animal source food due to its constituent complexity. In this study, a novel detection system was developed to quantify the contents of both free and conjugated methenolone in animal source food including pork, beef, mutton, milk, and eggs by using high‐performance liquid chromatography‐tandem mass spectrometry (HPLC‐MS/MS) coupled with delicate pretreatment procedures. The conjugated methenolone in the above food samples was released by dual enzyme digestion, and the total methenolone was extracted by 1% formic acid in acetonitrile, followed by the purification using a PRiME HLB column or QuEChERS (Quick, Easy, Cheap, Effective, Rugged, and Safe) salt. The compound d3 ‐methyltestosterone was used as an internal standard to minimize matrix interference. Finally, a wide linear range (0.5–20 μg/kg), low limit of detection (LOD) (0.3 μg/kg), good precision (<7% relative standard deviation), and high recovery (>90%) were obtained in the study of method validation. In summary, this analytical method provides a practicable monitoring tool for the quantification of methenolone in animal source food. Abstract : A novel and stable HPLC‐MS/MS method was developed for detecting methenolone in various food samples including meat, eggs, and milk.